Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Faraji Vásquez, Sofía (2018)
The present case prepares a strategic analysis of the Fast Retailing business group in order to prepare a proposal to introduce the brand into the Peruvian market while maintaining the structure of a strategic plan. Fast Retailing is a company oriented towards customer satisfaction and also oriented on the generation of added value for the whole society with a clear expansion strategy. For this reason, in the first chapter of the report an internal diagnosis of the company is prepared, starting with its business model and value chain to identify the main key activities and in this way, to be able to define its strengths and weaknesses, as well as Its competitive advantages. In addition, in order to determine whether income is feasible, an external analysis was prepared in order to know the market conditions, identifying the main factors of the macro environment and analyzing the main competitive forces of the Peruvian retail and sector that could favor or hinder such income. In the second chapter, the strategies of the Fast Retailing business units were formulated, the mission, vision and strategic objectives of the company were analyzed; The report then proposed a redefinition of the strategic units and the creation of a new strategic unit and the strategies they will need to implement to carry out the proposal. In the third chapter, the proposal of the organizational structure that should be implemented to facilitate the activity and support the business model according to the main key activities of the group is detailed. Likewise, changes were proposed to improve the implementation of Fast Retailing strategies, focusing on the four basic aspects such as the organization, management systems, key areas and people. In the fourth chapter, control mechanisms and key indicators are established to measure and ensure a correct implementation of the strategy that is geared towards Fast Retailing's objectives of offering maximum customer satisfaction and obtaining returns from its new market expansion. Finally, it is concluded that this solid group has all the capacity, market knowledge and strengths in its processes that will allow it to establish a new business in Perú.